Hope as Grounds for Forgiveness - Giannini, Heidi Chamberlin (Journal of religious ethics, 2017)
It is widely assumed that Christianity enjoins its followers to practice universal, unconditional forgiveness. But universal, unconditional forgiveness is regarded by many as morally problematic. Some Christian scholars have denied that Christianity in fact requires universal, unconditional forgiveness, but I believe they are mistaken. In this essay, I show two things: (1) that Christianity does enjoin universal, unconditional forgiveness of a certain sort, and (2) that Christians, and perhaps other theists, are always justified in exercising unconditional forgiveness. Though most philosophers treat forgiveness as grounded in our beliefs about the offender's current state, I argue that we might more fruitfully ground forgiveness in hope for the wrongdoer. Christianity's commitment to the existence of an omnipotent God who is concerned about the moral status of His creatures always justifies such hope and thus always justifies forgiveness.